Temporal Trends in Biologic Prescriptions for Patient with Inflammatory Bowel Disease: A Retrospective Cohort Study - Sunimal Fernando; Reeham Abu-Rgeef; Shankar Menon; Kenji So; Kannan Venugopal; Sherman Picardo (Gastroenterology Insights)
Background: Biologic therapies, such antitumour necrosis factor-alpha agents (infliximab and adalimumab), as well as newer agents (ustekinumab and vedolizumab), all have well-demonstrated safety and efficacy profiles in the management of inflammatory bowel disease (IBD). The choice of an optimal first-line biologic remains unclear due to a lack of comparative randomised trials and real-world studies; however, certain patient and disease characteristics may influence this choice. The aims of this study were to explore temporal trends in the choice of a first-line biologic therapy and the factors that influence this choice. Methodology: This study is a retrospective observational cohort study of all patients with IBD who commenced induction and completed at least one maintenance dose of a biologic therapy between 1 January 2015 and 31 December 2021. Relevant patient and disease-specific factors were collected, including history of malignancy and opportunistic infections at time of diagnosis, for each eligible patient. Factors affecting the choice of biologic therapy were compared using ANOVA and chi-square tests. Results: 280 patients were included in the study. Ustekinumab has overtaken infliximab and adalimumab as the first-line choice for Crohn’s disease since its introduction in 2018. Infliximab has remained the preferred first-line therapy for ulcerative colitis over adalimumab and vedolizumab. Ustekinumab has become he preferred biologic agent for older patients and those with a history of malignancy. Conclusions: Whilst an older agent such as infliximab is still preferred for the management of UC, novel agents such as ustekinumab are now more readily considered as a first-line agent for the management of CD.